Constructing the 'Child at Risk' in Social Work Reports: A Way of Seeing is a Way of not Seeing. (May 2015) - Roets, Griet; Rutten, Kris; Roose, Rudi; Vandekinderen, Caroline; Soetaert, Ronald
<x xml:space="preserve">Abstract</x> In the context of the changing relationship between children, parents and the welfare state, professionals have to deal with notions of the 'child at risk'. In child welfare and protection, the issue of normative judgement in (risk) assessment and documentation is an essential area for exploration for social workers. We examine the practice of report writing in which future professionals exercise power while assessing, documenting and judging the child as 'at risk'. We report on a study about a fictional social work case conducted with 152 students in Belgium, in which we developed a rhetorical analysis of the 'terministic screens' used in writing reports.